Our experience with cardiac MRI in a tertiary health care center in Nepal - Neupane, Nirmal Prasad; Rajlawot, Kritisha; Adhikari, Chandra Mani; Tamrakar, Rikesh; Prajapati, Dipanker; Simkhada, Rabindra; Joshi, Surakshya; Timilsena, Birat Krishna; Shahi, Ravi; Koirala, Parash; Aryal, Marisha; Timala, Rabindra Bhakta; et al. (Nepalese Heart Journal, 2024)
Background and Aim: Cardiac Magnetic Resonance (CMR) is a crucial noninvasive imaging technique for the thorough evaluation of the heart in various cardiovascular conditions. The potential to offer quantitative data on cardiac perfusion and function make CMR an exceptional choice of imaging for providing functional and morphological information about the heart. We performed cardiac MR evaluation of patients over a period of 12 months. Our aim was to establish the common cardiac MR indications and the diagnoses in diferent age groups in our population.Method: A retrospective analysis of patients undergoing CMR at Shahid Gangalal National Heart Center, Kathmandu, Nepal over a period of 12 months, from October 2021 to September 2022 was done. All patients who underwent cardiac MRI at our center, irrespective of age, sex, and indication were included in the study. A total number of 392 patients were included in our study who had undergone Cardiac MRI on a 3Tesla platform at our center. The respective protocols, tailored to the disease being investigated, were followed based on the indication of each patient. Data were entered in a predesigned proforma and SPSS was used for the analysis.Results: The most common indication to perform CMR at our centre was found to be the myocardial viability test. Among 147 patients (37.5 % of the study population) assessed for myocardial viability, 120 (81.6 %) showed infarction in the left anterior descending (LAD) territory, 17 (11.5 %) showed infarction in the LCX territory and 10 (6.8 %) showed RCA territory infarction. The most common cardiomyopathy diagnosed with cardiac MRI at our center was hypertrophic cardiomyopathy (HCM) (15.5 %), followed by dilated cardiomyopathy (DCM) (10.0 %). Other various cardiac MR diagnoses of patients were congenital heart disease (CHD) (5.8 %), arrhythmogenic right ventricular cardiomyopathy (ARVC) (5.6 %), myocarditis (3.0 %), valvular heart disease (VHD) (3.0 %), , cardiac mass/pseudo mass (2.0 %), pericarditis (1.7 %), and others (3.3 %). 48 patients that represents about 12.2 % of the total study population who underwent cardiac MRI at our centre had normal CMR fndings. Conclusion: Cardiac MRI is an excellent imaging modality in the evaluation of diferent groups of cardiovascular diseases. It does not only provide the diagnosis but also helps in evaluating the prognostic parameters in diferent cardiac patients. Hence, the use of CMR is encouraged in clinical practice in our setting to implement early and appropriate therapies in cardiac patients that may ultimately improve patient outcomes.